2013
DOI: 10.1371/journal.pone.0071023
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Uromodulin Excretion Predicts Progression of Chronic Kidney Disease Resulting from IgA Nephropathy

Abstract: BackgroundUromodulin, or Tamm-Horsfall protein, is the most abundant urinary protein in healthy individuals. Recent studies have suggested that uromodulin may play a role in chronic kidney diseases. We examined an IgA nephropathy cohort to determine whether uromodulin plays a role in the progression of IgA nephropathy.MethodsA total of 344 IgA nephropathy patients were involved in this study. Morphological changes were evaluated with the Oxford classification of IgA nephropathy. Enzyme Linked Immunosorbent Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
3
29
0
2
Order By: Relevance
“…The relationship To date, most published studies exploring the association between uromodulin and kidney function concentrated on urinary uromodulin levels. 7,8,[25][26][27] The most recent study by Garimella et al 25 examined the predictive value of uromodulin excretion in urine to assess the progress of kidney disease and all -cause mortality in a large elderly population, including 2948 participants of the Framingham Heart Study. The higher levels of urinary uromodulin were associated with a reduced risk of progression of kidney disease and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship To date, most published studies exploring the association between uromodulin and kidney function concentrated on urinary uromodulin levels. 7,8,[25][26][27] The most recent study by Garimella et al 25 examined the predictive value of uromodulin excretion in urine to assess the progress of kidney disease and all -cause mortality in a large elderly population, including 2948 participants of the Framingham Heart Study. The higher levels of urinary uromodulin were associated with a reduced risk of progression of kidney disease and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms previous cautionary observations about the measurement of urinary UMOD levels as a potential CKD biomarker. Recent studies have suggested that urinary levels collected outside the context of acute kidney injury are a useful biomarker of tubular reserve, UMOD genotype and renal prognosis (Han et al 2013;Trudu et al 2013;Zhou et al 2013;Devuyst and Bochud 2015;Garimella et al 2015;Pruijm et al 2016;Troyanov et al 2016). However, these assays impose significant technical challenges related to sample handling, as this disulfide-bond-rich glycoprotein readily self-aggregates and forms precipitates (Youhanna et al 2014), casting doubt on its practical utility as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the urinary excretion of B2M, cystatin C, osteopontin, and uromodulin have been associated with varying forms of kidney injury, 27,33,[50][51][52][53][54][55]231 but were not different between preeclampsia cases and controls. Increased urine NGAL has been associated with acute kidney injury, 51,56,57 but we found levels to be decreased in preeclampsia.…”
Section: Discussionmentioning
confidence: 99%